ANALISIS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN CORPORATE IMAGE SERTA DAMPAKNYA TERHADAP LOYALITAS KONSUMEN PT TELKOM DAERAH MERAUKE - Candra Agus Wahyudi Rahman; Maat Pono; Andi Nur Bau Massepe (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Every company has responsibility for its actions and business activities that have an impact, either directly or indirectly on the stakeholders and the environment in which the company is located. The profits of a company are not always measured by money alone but social benefits are also a matter of concern, whereby these social benefits in time will have a huge role for the existence of a company in the long term. This research aims to know to know the influence of Corporate Social Responsibility (CSR) Program and Corporate Image on Consumer Loyalty of PT Telkom in Merauke area. The approach used in this research is by using quantitative method approach, analyzing Corporate Social Responsibility Program (CSR) And Corporate Image (Corporate Image) And Its Impact On Consumer Loyalty with Quantitative Research Method which based on positivism philosophy, used to research on population or specific samples, data collection using research instruments, quantitative / statistical data analysis, with the aim to test the hypotheses that have been established ". The result of test that has been done shows that there is influence between Corporate Social Responsibility (CSR) with Corporate Image, there are positive and significant influence of Corporate Social Responsibility variable to Consumer Loyalty, Positive and Significant influence between Corporate Image and Consumer Loyalty, indirectly between the variables of Corporate Social Responsibility to Consumer Loyalty through the variable Corporate Image PT Telkom Merauke Region.